A comprehensive micro-nano investigative approach to study the development of aluminosilicate gel in binary blends of lithium slag geopolymer - Javed, Usman; Shaikh, Faiz; Sarker, Prabir (2024)
This study extensively investigates the formation of aluminosilicate gel in binary blends of lithium slag geopolymer (LSG) containing fly ash and silica fume. A comprehensive analysis of the aluminosilicate gel was performed at the micro-nano scale, employing techniques such as mineralogical, crystallographic, micromorphological, and micromechanical analysis. C-(N)-A-S-H and N-(C)-A-S-H gels were found between Si/Al ratios of 2.41–3.04 and 3.88 to 4.33, respectively. Fly ash incorporated LSG at 45% alkaline activator yielded the highest average nano-indented modulus of 22.54 GPa. Statistical Gaussian deconvolution was employed to categorize mineral phases in nano-indentation of LSG, revealing substantial distinctions indicated by the low p-values. Carbonation in silica fume incorporated LSG was affirmed by selected area electron diffraction (SAED) patterns of calcite crystallites. The microstructure of LSG containing fly ash was stiffened by the growth of needle crystals of hydroxy-sodalite and aluminosilicate gel. Thus, the formation of C-(N)-A-S-H gel and hydroxy-sodalite governs the strength development of LSG binary blends.